Impact of pre‐transplant biopsy on 5‐year outcomes of expanded criteria donor kidney transplantation. Issue 1 (8th October 2020) - Yap, Yun Ting; Ho, Quan Yao; Kee, Terence; Ng, Chee Yong; Chionh, Chang Yin
Abstract: Aim: Compared to Standard Criteria Donors (SCD), Expanded Criteria Donor (ECD) kidneys are associated with poorer outcomes, although pre‐transplant biopsy may mitigate risks. This study assessed 5‐year outcomes of deceased‐donor kidney transplant recipients, comparing recipients of ECD allografts evaluated histologically to recipients of SCD and ECD kidneys assessed clinically. Methods: This is a single‐centre retrospective study. From November 2005 to December 2009 (Era 1), donors were assessed clinically for suitability for kidney donation. From December 2009 to October 2017 (Era 2), kidneys from ECDs and diabetics underwent pre‐transplant biopsy and were allocated based on Remuzzi score. Outcomes of Era 1 and 2 recipients were compared. Results: ECD kidney transplantation increased from 30.4% to 40.0% from Era 1 to 2. Univariable Cox regression, stratified by transplant era, found that 5‐year graft loss was highest with Era 1 ECD (HR 2.5, 95% CI 1.1‐5.5, P = .027) while graft loss for Era 2 ECD recipients was similar to SCD recipients. There was no difference in 5‐year recipient survival. Amongst Era 1 ECD recipients, 51.2% experienced rejection compared to 30.8‐41.5% for other subgroups. Five‐year eGFR was higher with Era 2 ECD at 48.4 (33.3‐60.7) ml/min/1.73 m 2 compared to 42.2 (35.8‐57.3) ml/min/1.73 m 2 for Era 1 ECD. However, these differences were not statistically significant. Conclusion: Introduction of pre‐transplant biopsy assessment may be associated with improved outcomes of ECD kidney recipients such that they are now comparable to SCD kidney recipients, with benefits persisting over 5 years. SUMMARY AT A GLANCE: This article examined the benefit of performing pre‐transplant kidney biopsies in expanded criteria deceased donors. The authors showed that this practice may be associated with improved outcomes. Over a 5 year follow‐up period, outcomes using expanded criteria donors were comparable to those with standard criteria donors.